Psychological Impact Of Mount Kelud Eruption On Children In (Ring 1) Desa Kebonrejo Village, Kepung, Kediri District; Qualitative Research - Bambang Wiseno; Nugrahaeni Firdaus; Maulana Rahmat Hidayatullah (STRADA : Jurnal Ilmiah Kesehatan, 2020)
Children who are a vulnerable group in disasters need special attention to reduce the negative risk of their life. This qualitative research with a phenomenological approach was conducted on children who survived the Mount Kelud eruption. Referring to the research aim and after analyzing the data with Interpretative Phenomenology Analysis (IPA), 6 (six) themes were found, namely: feeling the need to pray a lot, feeling afraid if the kelud volcano erupts again, the more affection for parents, feeling afraid of death, feeling slopes Kelud is the land of birth, and feels uncomfortable in the refuge. From all the themes can be concluded that the children who survived the 2014 eruption of Mount Kelud still felt frightened by the condition of Mount Kelud that might erupt, making them more prayerful and happy to help their parents because they didn't want their parents to be difficult.